Peering inside the peak ring of the Chicxulub Impact Crater—its nature and formation mechanism. (26th March 2019) - Urrutia‐Fucugauchi, Jaime; Pérez‐Cruz, Ligia; Morgan, Joanna; Gulick, Sean; Wittmann, Axel; Lofi, Johanna; ,
Abstract : The IODP‐ICDP Expedition 364 drilled into the Chicxulub crater, peering inside its well‐preserved peak ring. The borehole penetrated a sequence of post‐impact carbonates and a unit of suevites and clast‐poor impact melt rock at the top of the peak ring. Beneath this sequence, basement rocks cut by pre‐impact and impact dykes, with breccias and melt, were encountered at shallow depths. The basement rocks are fractured, shocked and uplifted, consistent with dynamic collapse, uplift and long‐distance transport of weakened material during collapse of the transient cavity and final crater formation.